Strategi Optimalisasi Produksi dan Keuntungan Ayam Geprek Menggunakan Metode Simplex: Studi Kasus Ayam Geprek AA Ray - Hidayah, Natari Dia Alika; Yanti, Evida; Pranata, Rio; Williandi, Bambang; Yehezkiel, Steven (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This research aims to assist Ayam Geprek restaurants in optimizing the production of Ayam Geprek using the simplex method. The primary objectives are: 1) To determine the ideal number of Ayam Geprek to be produced to maximize profits, 2) To analyze whether the current production of Ayam Geprek has already achieved maximum profitability, 3) To assess the efficiency of raw material and resource utilization in the production process, and 4) To evaluate the impact of the simplex method on profit changes and resource utilization. Data for the research was collected through direct observation, involving information about raw materials, labor, and customer demand. The analysis was conducted using QM for Windows software to determine the optimal results. The findings indicate that the simplex method can help improve efficiency, utilize resources more effectively, and maximize profits.Warung Makan Ayam Geprek AA Ray faces challenges in managing production optimally to maximize profits. Based on both manual calculations and the simplex method using QM for Windows, it was found that the maximum profit of 850,000 can be achieved by producing 0.5 units of Ayam Geprek (X1) and 3 units of Lele Geprek (X2).